1980
DOI: 10.1001/archinte.140.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor performance defects in cirrhotic patients without overt encephalopathy

Abstract: Psychometric tests were administered to 36 alcoholic patients with cirrhosis without overt portal systemic encephalopathy and to 32 alcoholics without liver diseases. Verbal ability was preserved in both groups. The cirrhotic patients scored worse than the alcoholics without liver disease on most of the tests of psychomotor performance. Based on the three most discriminative tests, 50% of the cirrhotic patients had one or more scores that were more abnormal than those of any member of the alcoholic group. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…defects, yet have a normal mental and neurological status on One hundred and thirty-seven consecutive patients global clinical examination. [3][4][5][6][7][8][9][10][11][12][13] The prevalence of this subclin-(mean age 49 years, range 17-77) with cirrhosis without ical hepatic encephalopathy (SHE) has been reported to vary any clinical signs of encephalopathy, were screened for from 30% 13 to 84%, 11 depending on the tests and population SHE. In addition, the Child-Pugh score and the arterial used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…defects, yet have a normal mental and neurological status on One hundred and thirty-seven consecutive patients global clinical examination. [3][4][5][6][7][8][9][10][11][12][13] The prevalence of this subclin-(mean age 49 years, range 17-77) with cirrhosis without ical hepatic encephalopathy (SHE) has been reported to vary any clinical signs of encephalopathy, were screened for from 30% 13 to 84%, 11 depending on the tests and population SHE. In addition, the Child-Pugh score and the arterial used.…”
mentioning
confidence: 99%
“…Two psychometric tests with age-corrected normal values (NCT part A, 30 Symbol Digit Test 31 ) were selected to be used as a neuropsychological screen. These two tests are easy to administer, have a reported high sensitivity in detecting SHE, [3][4][5]8,9,12,13 and can be performed within 5 Pugh score was determined to assess the severity of the …”
mentioning
confidence: 99%
“…In fact, a relationship has already been found between albumin plasma level and mental derangement in cirrhotics (Gilberstadt, 1980, Schomerus et al, 1981.…”
Section: Neuropsychological Assessmentmentioning
confidence: 89%
“…(1978) suggested that the Wechsler Adult Intelligence Scale (WAIS) performance test, the Reitan-A and B tests, and choice reaction time to light and sound have the best diagnostic values . The usefulness of the WAIS performance group test was later confirmed by Gilberstadt et al (1980), who found that the most useful tests are the Digit Symbol and the Block Design tests . Also Tarter et al .…”
Section: Introductionmentioning
confidence: 92%
“…11,12 This comprises a subset of cirrhotic patients who do not show clinically overt symptoms of HE, but display abnormal neuropsychologic and/or neurophysiologic findings indicative of cerebral dysfunction. 13 Importantly, there is some evidence that traditional treatments for overt HE also improve this minimal HE. 14 Accordingly, it may be reasonable to test drugs for efficacy in overt HE by first establishing their capacity to improve or reverse minimal HE.…”
Section: Commentsmentioning
confidence: 99%